2016
DOI: 10.1108/sef-03-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and acquisitions: a review. Part 1

Abstract: Purpose – This paper aims to review the relevant literature on mergers and acquisitions in an attempt to provide a comprehensive account of what we know about mergers and which parts of the puzzle are still incomplete. Design/methodology/approach – This literature review consists of three key sections. The first part of this paper summarises the literature on the cyclical nature of mergers referred to in the literature as merger waves. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 247 publications
2
25
0
Order By: Relevance
“…CARs for (+1;-1) in Yilmaz and Tanyeri (2016), Kinateder et al 2017 andYaghoubi et al 2016a and 2016b are statistically significant. More, Yaghoubi et al 2016a and2016b show that the abnormal performance in mergers is statistically significant. The statistical significance of differences in means might be interpreted as illustrating that contributions of acquirers and target firms to the merged entity are different.…”
Section: (Excess) Returnsmentioning
confidence: 87%
See 3 more Smart Citations
“…CARs for (+1;-1) in Yilmaz and Tanyeri (2016), Kinateder et al 2017 andYaghoubi et al 2016a and 2016b are statistically significant. More, Yaghoubi et al 2016a and2016b show that the abnormal performance in mergers is statistically significant. The statistical significance of differences in means might be interpreted as illustrating that contributions of acquirers and target firms to the merged entity are different.…”
Section: (Excess) Returnsmentioning
confidence: 87%
“…The apparent premiums inSorwar and Sudarsanam (2010) are £0.34 and £0.37 for entire and continuous ) found that more (less) premium goes to target (acquiring) shareholders. WhileYaghoubi et al 2016a found premium is caused by either valuation error or hubris. Valuation error is applicable to the study as real estate appraisers are all to some level to misprice properties.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…According to Yaghoubi et. al (2016), the motives for a merger or an acquisition can be gathered into four groups: managerial theories, industry-level theories, economic conditions, and behavioral theories.…”
Section: Motives For Merger and Acquisitionmentioning
confidence: 99%